PENGARUH POLA KOMUNIKASI KELUARGA TERHADAP KEPUTUSAN MEMILIH PERGURUAN TINGGI (Studi Pada Orang Tua Mahasiswa Ilmu Komunikasi UPN Veteran Jakarta). - Yusa Maliki Santoro, (2021)
Family communication usually has more personal problems than other group communication. One of the problems in family communication is determining the college. Then in a family must plan education for the future of the child. The pattern of communication in a family is also a way to compromise the education choices that will be taken by family members. This study aims to determine the influence and magnitude of the influence of family communication patterns on the decision to choose a college. This study uses the theory of family communication patterns created by Mary Anne Fitzpatrick. The research method used in this research is an explanatory quantitative method using probability sampling technique with the number of respondents as many as 92 parents of Communication Science Students of UPN Veteran Jakarta. The results of this study indicate that the correlation value shows a significance of 0.000 which indicates a correlation because the value is <0.05. The calculated r coefficient of 0.265 indicates that there is a weak correlation. The results of the regression test showed that the influence of family communication patterns on the decision to choose a college was positive. The results of the coefficient of determination indicate that there is an influence of 16.6% between the influence of family communication patterns on the decision to choose a college. These results are strengthened by hypothesis testing which states that H0 is rejected and H1 is accepted, meaning that there is an influence of family communication patterns on the decision to choose a college. The conclusion of this study is that family communication patterns have an influence on the decision to choose a college, especially for parents of Communication Science Students of UPN Veteran Jakarta.